# Derivative of 1/x^2: by First Principle, Power and Product Rule

The derivative of 1/x2 is equal to -2/x3. In this article, we will learn how to find the derivative of 1 divided by x2 using the power rule, product rule, and the definition of derivatives.

## Derivative of 1/x2 Formula

Note that 1/x2 is an algebraic function. The derivative of 1/x2 can be expressed as d/dx(1/x2) or (1/x2)$’$. The derivative formula of 1 divided by x square is given below:

d/dx(1/x2) = -2/x3 or (1/x2)$’$ = -2/x3.

## What is the Derivative of 1/x2?

Derivative of 1/x2 by power rule: Let us first find the derivative of 1 by x2 by the power rule of derivatives. Recall the power rule of derivatives: d/dx(xn) = nxn-1.

Follow the below steps to find the differentiation of 1 divided by x2.

Conclusion: The derivative of 1/x2 by power rule is -2/x3.

## Derivative of 1/x2 by First Principle

If f(x) is a function of real variable x, then the derivative of f(x) by the first principle is given by the following limit formula:

$\dfrac{d}{dx}(f(x))$ = limh→0 $\dfrac{f(x+h)-f(x)}{h}$

Put f(x) = 1/x2

So the derivative of 1/x2 from first principle is

$\dfrac{d}{dx}\big(\dfrac{1}{x^2} \big)$ = limh→0 $\dfrac{\frac{1}{(x+h)^2}-\frac{1}{x^2}}{h}$

= limh→0 $\dfrac{x^2-(x+h)^2}{hx^2(x+h)^2}$

= limh→0 $\dfrac{x^2-(x^2+2xh+h^2)}{hx^2(x+h)^2}$

= limh→0 $\dfrac{-h(2x+h)}{hx^2(x+h)^2}$

= limh→0 $\dfrac{-(2x+h)}{x^2(x+h)^2}$

= $\dfrac{-(2x+0)}{x^2(x+0)^2}$

= $\dfrac{-2x}{x^4}$ = $-\dfrac{2}{x^3}$.

Thus, the derivative of 1/x2 is equal to -2/x3 and this is obtained from the first principle of derivatives.

## Derivative of 1/x2 by Product Rule

Now, we will find the derivative of 1/x2 by the substitution method together with the product rule of derivatives. For this let us put

z=1/x2. We need to find dz/dx.

This implies that

zx2=1

Differentiating with respect to x, we get that

$\dfrac{d}{dx}(zx^2)=\dfrac{d}{dx}(1)$

⇒ $z\dfrac{d}{dx}(x^2)+x^2\dfrac{d}{dx}(z)=0$ (by the product rule of derivatives)

⇒ z⋅2x + x2 $\dfrac{dz}{dx}$ = 0

⇒ $x^2\dfrac{dz}{dx}=-2zx$

⇒ $\dfrac{dz}{dx}=-\dfrac{2z}{x}$

⇒ $\dfrac{dz}{dx}=-\dfrac{2}{x^3}$ as z=1/x2

So we have obtained the differentiation of 1/x2 by the product rule which is -2/x3.

Also Read: How to Differentiate 1/x3?

## Solved Problems

Question: Find the derivative of 1/sin2x.

Let z=sinx.

So dz/dx = cosx.

So by the chain rule, the derivative of 1/sin2x is equal to

d/dx (1/sin2x)

= $\dfrac{d}{dz}(\dfrac{1}{z^2}) \times \dfrac{dz}{dx}$

= $-\dfrac{2}{z^3} \times \cos x$, by the above differentiation rule of 1/x2.

= $-\dfrac{2\cos x}{\sin^3 x}$ as z=sinx.

So the derivative of 1/sin2x is equal to -2cosx/sin3x, obtained by the chain rule of derivatives.

## FAQs on Derivative of 1/x2

Q1: What is the derivative of 1/x2?

Answer: The derivative of 1/x2 (1 over x square) is equal to -2/x3.

Q2: What is the derivative of x2?

Answer: The derivative of x2 (x square) is 2x.

Share via: